2015
DOI: 10.1038/npp.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Cue-Induced Motivation and Striatal Systems in Rats Susceptible to Diet-Induced Obesity

Abstract: Pavlovian cues associated with junk-foods (caloric, highly sweet, and/or fatty foods), like the smell of brownies, can elicit craving to eat and increase the amount of food consumed. People who are more susceptible to these motivational effects of food cues may have a higher risk for becoming obese. Further, overconsumption of junk-foods leading to the development of obesity may itself heighten attraction to food cues. Here, we used a model of individual susceptibility to junk-foods diet-induced obesity to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
152
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(172 citation statements)
references
References 49 publications
17
152
2
1
Order By: Relevance
“…We propose that this is due to a change in response priority due to the incentive value of the food and not a change in Pavlovian or instrumental learning, as obese rats were capable of both appetitive and aversive conditioning. Consistent with these findings, others have demonstrated that cafeteria-diet-induced obesity show increased conditioned approach behaviours likely to due to the enhanced incentive value of the food without a change in the rate of acquisition of Pavlovian learning (Robinson et al, 2015). Rats with restricted access to a cafeteria diet exhibited binge-like eating behaviour such that they consumed 2/3 of their daily caloric needs within 1 h and that they had elevated baseline feeding in the operant chambers compared to extended access rats.…”
Section: Discussionsupporting
confidence: 72%
“…We propose that this is due to a change in response priority due to the incentive value of the food and not a change in Pavlovian or instrumental learning, as obese rats were capable of both appetitive and aversive conditioning. Consistent with these findings, others have demonstrated that cafeteria-diet-induced obesity show increased conditioned approach behaviours likely to due to the enhanced incentive value of the food without a change in the rate of acquisition of Pavlovian learning (Robinson et al, 2015). Rats with restricted access to a cafeteria diet exhibited binge-like eating behaviour such that they consumed 2/3 of their daily caloric needs within 1 h and that they had elevated baseline feeding in the operant chambers compared to extended access rats.…”
Section: Discussionsupporting
confidence: 72%
“…A central observation is that, compared with normal weight controls, overweight and obese humans show reduced striatal D2R availability Stice et al, 2008b;Kenny et al, 2013) and individuals with the Taq1A A1 allele, which is associated with reduced D2R expression, are more likely to be obese (Stice et al, 2008b). Obese and overweight individuals also show enhanced striatal activation in response to food-predictive cues (Rothemund et al, 2007;Stoeckel et al, 2008;Demos et al, 2012), but reduced striatal activation following palatable food receipt (Stice et al, 2008a, b;Babbs et al, 2013). Importantly these striatal reactivity observations, which may reflect reward prediction error signals (Kroemer and Small, 2016), are also predictive of future weight gain, indicating that striatal network activity is closely linked with the development of obesity Demos et al, 2012).…”
Section: Altered Striatal Function and Obesitymentioning
confidence: 99%
“…However, reduced striatal D2R expression is seen in rodents fed a junk-food diet regardless of the whether they develop obesity or not (Robinson et al, 2015), suggesting that this striatal adaptation cannot fully explain maladaptive weight gain (Kroemer and Small, 2016). A more parsimonious explanation emerging from the literature is one in which individual susceptibility interacts with the types of foods consumed to alter striatal function and promote cue-induced food-seeking behavior (Stice et al, 2008b(Stice et al, , 2009Stoeckel et al, 2008;Felsted et al, 2010;Albuquerque et al, 2015;Brown et al, 2015b;Robinson et al, 2015). This chain of events may then be further exacerbated by increased adiposity and metabolic dysfunction that characterize obesity.…”
Section: Altered Striatal Function and Obesitymentioning
confidence: 99%
See 2 more Smart Citations